2010
DOI: 10.1086/652432
|View full text |Cite
|
Sign up to set email alerts
|

Make Love Not War: When Should Less Competitive Males Choose Low‐Quality but Defendable Females?

Abstract: Male choosiness for mates is an underexplored mechanism of sexual selection. A few theoretical studies suggest that males may exhibit--but only under rare circumstances--a reversed male mate choice (RMMC; i.e., highly competitive males focus on the most fecund females, while the low-quality males exclusively pair with less fecund mates to avoid being outcompeted by stronger rivals). Here we propose a new model to explore RMMC by relaxing some of the restrictive assumptions of the previous models and by conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 39 publications
(44 reference statements)
1
70
0
Order By: Relevance
“…Recent theoretical models and empirical studies, however, have made a compelling case that male choice can be expected under a relatively wide range of conditions (Rowell and Servedio 2009;Venner et al 2010), and male choice is now known to be taxonomically widespread (Amundsen 2000;Bonduriansky 2001;Edward and Chapman 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical models and empirical studies, however, have made a compelling case that male choice can be expected under a relatively wide range of conditions (Rowell and Servedio 2009;Venner et al 2010), and male choice is now known to be taxonomically widespread (Amundsen 2000;Bonduriansky 2001;Edward and Chapman 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because competition among males can mediate choice, selection does not easily favor identical male mating preferences for all males, as the mean mating value of a female declines as the number of males she attracts increases (Servedio and Lande 2006;Servedio 2007). Because of this, male mate choice evolves considerably more easily when males can alter their mate preferences and reproductive behavior in response to the level of competition (Fawcett and Johnstone 2003;Härdling and Kokko 2005;Rowell and Servedio 2009;Venner et al 2010). Empirically, males are known to change their mate preferences in response to social factors such as competition from rival males (Bel-Venner et al 2008;Candolin and Salesto 2009), their recent history of mate encounters (Jordan and Brooks 2012), or the reactions of courted females (Patricelli et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, this applies only if the number of mating partners exceeds the potential mating rate of the male (Härdling and Kokko 2005). On the contrary, poor competitors have less mating opportunities and should mate with every available female or even prefer low quality females to further reduce the level of male-male competition (Bel-Venner et al 2008, Venner et al 2010). This could also make low quality males more susceptible to hybridization.…”
Section: Intrasexual Competitive Environmentmentioning
confidence: 99%
“…In some crustaceans where males show precopulatory guarding behavior and compete for mates, males are known to have thresholds for female sexual receptivity (Manning 1980;Dick and Elwood 1989;Wada et al 1999). Male mate choice and male-male competition potentially will have effects on each other, and some theoretical models predict that competitive dominance of males could lead to variation in the direction and strength of male mate choice (Fawcett and Johnstone 2003;Härdling et al 2004;Härdling and Kokko 2005;Venner et al 2010). Wada et al (2011) demonstrated that inferior small males of the hermit crab, Pagurus middendorffii, choose not only larger females but also females that require less time to guard until prenuptial molting and/or spawning, while large superior males choose females based on their body size.…”
Section: Introductionmentioning
confidence: 99%